Histological Changes Related to Symptomatic Improvement of Spontaneous Keloids Treated with a Low-Dosage Regimen of UVA-1 Phototherapy - Carlos Cuenca-Barrales; José Aneiros-Fernández; Israel Pérez-López; Julia Rodríguez-Pérez; Ricardo Ruiz-Villaverde; Jorge Luis Espelt-Otero (MDPI AG, 2020)
Keloids are a difficult-to-treat disease characterized by an imbalance in mechanisms of tissue reparation. We present the case of a middle-aged woman with spontaneous keloids which histologically and clinically improved after UVA-1 phototherapy treatment. There are few reported cases of keloids treated with high doses of UVA-1 phototherapy. We used a low-dosage regimen with a good response in only one cycle, which could diminish the risk of skin cancer development.